Are market‐based solutions a viable strategy for addressing micronutrient deficiency? Lessons from case studies in sub‐Saharan Africa and South Asia. (8th November 2020) - Henson, Spencer; Agnew, Jessica
Abstract: Motivation: While public and civil sector nutrition interventions in low‐ and middle‐income countries have demonstrated positive impacts on nutritional status, micronutrient deficiency remains persistent and severe. Accordingly, there is much debate about the viability of market‐based strategies directed at reducing micronutrient deficiencies among the poor, particularly concerning the role businesses can take. Purpose: This article explores the potential for both large and micro/small businesses to engage in markets for nutrient‐dense foods. It examines the challenges businesses face in establishing and maintaining sustainable business models and whether these businesses can achieve the scale required to achieve substantive impacts on the nutrition of the poor. Methodology: This article presents a comprehensive literature review and in‐depth case studies of market‐based initiatives directed at enhancing the access of the poor to nutrient‐dense foods. The case studies involved analysis of secondary data and interviews with stakeholders, including value chain actors, civil society organizations, government officials, etc. Findings: All bottom of the pyramid (BOP) businesses face considerable challenges in the context of markets for nutrient‐dense foods directed at the poor that relate to the difficulties faced in presenting a viable value proposition to consumers and in distributing products to the places where the poor reside, while achieving sustainable scale. Importantly, the results indicate a critical role for micro/small businesses in promoting the consumption of nutrient‐dense foods by the poor. Policy implications: The findings raise important questions over the role and focus of public support to businesses looking to enter and/or expand in markets for nutrient‐dense foods directed at the poor, and especially with respect to micro/small businesses as opposed to large/multinational corporations. Originality: The article presents the first comparative analysis of market‐based strategies of micro/small to large businesses directed at reducing micronutrient deficiencies in the poor.